2012
DOI: 10.1590/s0100-40422012001000013
|View full text |Cite
|
Sign up to set email alerts
|

Análises quali e quantitativas de micotoxinas em águas da cadeia produtiva do arroz por CCD e CCDAE

Abstract: Universidade Federal do Rio Grande, CP 474, 96201-900 Rio Grande -RS, BrasilRecebido em 20/2/12; aceito em 4/7/12; publicado na web em 17/9/12 QUALITATIVE AND QUANTITATIVE MYCOTOXIN ANALYSES IN RESIDUAL WATER OF RICE PRODUCTION CHAIN BY TLC AND HPTLC. This study validated a simple and applied method for determining mycotoxins aflatoxin B 1 , aflatoxin B 2 , ochratoxin A, zearalenone and deoxynivalenol, in water from the rice production chain. Five solvent combinations for extraction were tested, with quantific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…-waters that flow or accumulate on the soil surface, rivers, streams, or lakes). The presence of DON in soil and plants (SCHENZEL et al, 2012), zearalenone in agricultural wastewater (HARTMANN et al, 2007;WAŚKIEWICZ et al, 2012) and aflatoxin B 1 and DON in wastewater from rice production (LEITE et al, 2012) were also observed by several authors. Such studies indicate that effluents can carry toxins naturally present in the grains, thus compromising the environment.…”
Section: Effect Of Ozonation On the Don Concentration In Wheat Wet MImentioning
confidence: 80%
“…-waters that flow or accumulate on the soil surface, rivers, streams, or lakes). The presence of DON in soil and plants (SCHENZEL et al, 2012), zearalenone in agricultural wastewater (HARTMANN et al, 2007;WAŚKIEWICZ et al, 2012) and aflatoxin B 1 and DON in wastewater from rice production (LEITE et al, 2012) were also observed by several authors. Such studies indicate that effluents can carry toxins naturally present in the grains, thus compromising the environment.…”
Section: Effect Of Ozonation On the Don Concentration In Wheat Wet MImentioning
confidence: 80%